Sing and shout : the mighty voice of Paul Robeson - Rubin, Susan Goldman (Calkins Creek, 2020)
Biography of African American bass-baritone singer Paul Robeson. Tracks his life and career through the twentieth century, how he used the spirituals he had heard in church and folk songs from around the world to sing about and combat injustices in the United States. At the height of the Cold War he lost his U.S. passport after being accused of being a communist, but that didn't stop Robeson from singing or giving in.